2022
DOI: 10.3389/fonc.2022.840433
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Performance of Maximum Uptake Value and Apparent Diffusion Coefficient in Differentiating Benign and Malignant Ovarian or Adnexal Masses: A Meta-Analysis

Abstract: ObjectiveThe purpose of this meta-analysis was to provide evidence for using maximum uptake value (SUVmax) and apparent diffusion coefficient (ADC) to quantitatively differentiate benign and malignant ovarian or adnexal masses, and to indirectly compare their diagnostic performance.Material and MethodsThe association between SUVmax, ADC and ovarian or adnexal benign and malignant masses was searched in PubMed, Cochrane Library, and Embase databases until October 1, 2021. Two authors independently extracted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Fluorodeoxyglucose (FDG) labeled with radionuclide 18 F is widely used in clinical practice and has been proved to be highly accurate in the differential diagnosis of benign and malignant ovarian masses ( 128 , 129 ). However, a study of 18 F-FDG PET/CT to evaluate the expression status of HER2 receptor has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorodeoxyglucose (FDG) labeled with radionuclide 18 F is widely used in clinical practice and has been proved to be highly accurate in the differential diagnosis of benign and malignant ovarian masses ( 128 , 129 ). However, a study of 18 F-FDG PET/CT to evaluate the expression status of HER2 receptor has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a subsequent quantitative investigation evaluating benign and malignant ovarian tumors through the PET/CT parameter SUVmax demonstrated similarly robust diagnostic performance. This analysis revealed that the SUVmax of benign and malignant ovarian tumors averaged 2.2 and 9.6, respectively 18 . The findings of our present study substantiate these previous research outcomes by highlighting a significant disparity in 18 F-FDG uptake between the MS and OC-PMS groups.…”
Section: Discussionmentioning
confidence: 95%
“…18 F-FDG PET/CT, which integrates morphological and metabolic function information, has been widely used in the diagnosis, preoperative staging, treatment and prognosis assessment of tumors, and has shown higher clinical application value than traditional imaging methods in the management of tumors 8 , 9 . The maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), total lesion glycolysis (TLG), tumor metabolic volume (MTV), the maximum tumor-to-mediastinum (blood pool of descending aorta) background ratio (TMR) and the maximum tumor-to-liver background ratio (TLR) as important metabolic parameters in PET/CT, have shown high diagnostic value in the differentiation of benign and malignant tumors 10 12 . Due to the rarity of cardiac tumors, there is currently limited research on the diagnosis and differentiation of cardiac tumors through PET/CT 13 15 .…”
Section: Introductionmentioning
confidence: 99%